Synthesis of Copper Nanoparticles and Their Antimicrobial Performances in Natural Fibres - Chowdhury, M. N. K.; Beg, M. D. H.; Khan, Maksudur R.; Mina, M. F. (Elsevier Ltd, 2012)
Copper nanoparticles (CuNPs) were synthesized at ambient atmospheric condition by the chemical reduction method. The reduction of the solution of copper chloride salt in the polyvinyl alcohol system was done by sodium borohydride solution. The ultraviolet–visible spectroscopy, Fourier transformed infrared spectroscopy, transmission electron microscopy and X-ray diffraction studies were employed to analyse the formations and sizes of nanoparticles. The average size of CuNPs was measured to be 3 nm. The synthesized CuNPs were impregnated in natural fibres and their antimicrobial performances were assessed against both the Gram-positive and Gram-negative bacteria, showing more antibacterial activity in Escherichia coli than Staphylococcus aureus along with ∼7% antifungal activity.